Development and application of two multiplex real-time PCR assays for detection and speciation of bacterial pathogens in the koala. (July 2018) - Hulse, Lyndal S.; Hickey, Danica; Mitchell, Jessica M.; Beagley, Kenneth W.; Ellis, William; Johnston, Stephen D.
Infectious diseases have contributed to the decline in the health of koala ( Phascolarctos cinereus ) populations in the wild in some regions of Australia. Herein we report the development and validation of 2 multiplex real-time PCR (rtPCR) panels for the simultaneous detection of Mycoplasma spp., Ureaplasma spp., Bordetella bronchiseptica, and Chlamydia, including speciation and quantification of Chlamydia, in ocular, reproductive, and nasal swab samples in addition to semen and male urogenital and reproductive tissues, from koalas. Each rtPCR panel was developed for use as a single-tube reaction using pathogen-specific primers and fluorescently labeled probe sets. DNA extracted from reference strains and isolates was used for validation of sequence gene targets for the multiplex rtPCR panels. Each panel was shown to be sensitive and specific in detecting and differentiating the bacterial pathogens. The multiplex rtPCR panels were used to screen clinical samples from free-ranging and hospitalized koalas for multiple pathogens simultaneously. The multiplex rtPCR will improve turnaround time compared to individual-pathogen rtPCR methods used, to date, for confirmation of diagnosis and will provide the wildlife clinician with the ability to make treatment decisions more rapidly.